1995
DOI: 10.1006/cbir.1995.1009
|View full text |Cite
|
Sign up to set email alerts
|

A GCN‐like response in Candida albicans.

Abstract: The control of amino acid and purine biosynthesis in the yeast Saccharomyces cerevisiae is mediated by the transcriptional activator GCN4. We previously identified the presence of two putative GCN4 responsive elements (GCREs) in the promoter sequence of the Candida albicans ARO3 gene, which encodes an enzyme in the aromatic amino acid pathway. We now show that amino acid deprivation results in a dramatic rise in the steady-state level of ARO3-specific mRNA, indicative of a GCN-like pathway in C. albicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…3 was simultaneously probed with a cDNA from the C. albicans CYP1 gene, encoding cytoplasmic cyclophilin, which recognizes an approximately 800 bp mRNA (Koser et al, 1990). The observed reduction in CYP1 mRNA in 3AT-treated cells is consistent with earlier findings, and is probably due to a drop in the overall rate of protein synthesis (Pereira & Livi, 1995). This result serves to accentuate the observed increase in ARO4-specific mRNA, and our estimates of the derepression ratio compare favourably with those of many starvation-induced genes in S. cerevisiae (data not shown ; Hinnebusch, 1990).…”
Section: Aro4 Mrna Levels Increase During Amino Acid Starvationsupporting
confidence: 91%
See 1 more Smart Citation
“…3 was simultaneously probed with a cDNA from the C. albicans CYP1 gene, encoding cytoplasmic cyclophilin, which recognizes an approximately 800 bp mRNA (Koser et al, 1990). The observed reduction in CYP1 mRNA in 3AT-treated cells is consistent with earlier findings, and is probably due to a drop in the overall rate of protein synthesis (Pereira & Livi, 1995). This result serves to accentuate the observed increase in ARO4-specific mRNA, and our estimates of the derepression ratio compare favourably with those of many starvation-induced genes in S. cerevisiae (data not shown ; Hinnebusch, 1990).…”
Section: Aro4 Mrna Levels Increase During Amino Acid Starvationsupporting
confidence: 91%
“…We previously cloned an ARO3 gene orthologue from the diploid pathogenic fungus C. albicans and found that it can complement an aro3 aro4 double mutation in S. cerevisiae, and that complementation is inhibited by excess phenylalanine (Pereira & Livi, 1993). Expression of C. albicans ARO3 mRNA is induced in response to amino acid starvation, consistent with the presence of two putative GCREs in the promoter sequence (Pereira & Livi, 1995). A homozygous aro3-deletion mutant strain was constructed and found to be prototrophic (Aro + ) on synthetic complete media lacking aromatic amino acids (Pereira & Livi, 1996), suggesting the existence of at least one additional isozyme.…”
Section: Introductionmentioning
confidence: 90%
“…2), while a putative transcription termination signal was at 2943-2967 (based on their homology to S. cerevisiae consensus signals). No obvious S. cerevisiae GCN boxes (consensus sequence TGACTC) could be found in the 5'-upstream region, as has been observed for the C. albicans AR03 (Pereira & Livi, 1995) and A R G 4 (Hoyer et al, 1994) genes. In addition to the arg4 mutant strains 1006 and TMSU221, another complementation group designated argIOO has been described for strains A642, hOG318, hOG357, FC18-6 and WC-5-4 (Hoyer et al, 1994) located on the R chromosome.…”
Section: Sequence Analysis Of the C Albicans Arg56 Genesupporting
confidence: 54%
“…Phosphorylation of eIF2␣ can induce gene-specific translation important for coordinate expression of genes required to remedy cellular stress. While GCN4 homologues are also found in many other fungi, including Neurospora crassa (43), Aspergillus niger (78), and Candida albicans (55), there is no GCN4 homologue in S. pombe or in higher eukaryotic organisms. In mammalian cells, translational expression of another bZIP protein, ATF4, has been reported to be induced by GCN2 and PEK/Perk in response to amino acid limitation and ER stress, respectively (27).…”
Section: Fig 8 Loss Of Hri1mentioning
confidence: 99%